Effect of ethanolic seed extract of Caesalpinia bonducella on hormones in mifepristone induced PCOS rats - Balasubramanian Meera Murugesan, Palayyan Muralidharan, Rajeswary Hari (Journal of Applied Pharmaceutical Science, 2020)
The aim of the current study is to evaluate the effect of ethanolic seed extract of Caesalpinia bonduella (ESECB) on altered hormonal levels in mifebristone-induced polycystic ovarian syndrome (PCOS) female rats. PCOS was induced in female rats by a daily administration of mifepristone (4 mg/kg b.w.) for 8 days which was confirmed by the persistent estrous cycle. Once PCOS was induced, the rats were treated with ESECB 200 and 400 mg/kg b.w. p.o. for 28 days, and the hormonal parameters were analyzed. Metformin was used as a standard drug. A significant increase (p < 0.01) in the luteinizing hormone, Prolactin, insulin, testosterone, estrone, and estradiol levels and decrease in follicle stimulating hormone and progesterone hormone levels in the PCOS rats were observed, which were normalized in the ESECB drug-treated animals. Among the two concentrations, 400 mg/kg b.w of ESECB drug treatment showed significant effect in correcting this hormonal imbalance. Its effect was comparable to the positive control used in the present study. It can be concluded that the ESECB can be used as a potential ovulation inducer in the treatment of PCOS.
Keywords: Caesalpinia bonducella, ESECB, PCOS, ifepristone